Akuntansi Hijau, Inovasi, dan Kinerja Keuangan: Analisis Peran CSR Sebagai Moderator - Tele, Mario Ferdinandus; Suhartini, Dwi (ARBITRASE: Journal of Economics and Accounting, 2025)
This study aims to analyze the influence of green accounting, environmental performance, green innovation, and company size on financial performance with corporate social responsibility as a moderating variable. This study employs a quantitative approach using classical assumption tests, multiple linear regression analysis, and moderated regression analysis processed using SPSS. The data analyzed consists of 636 observations from 106 manufacturing companies listed on the Indonesia Stock Exchange and participating in the PROPER program during the 2022–2023 period. The results indicate that green accounting and firm size have a significant positive impact on financial performance, with disclosure levels reaching 93% and average firm assets of 29.64. Conversely, environmental performance and green innovation have a significant negative impact, with an average score of 3.14 for environmental performance (dominated by PROPER Blue) and green innovation implementation at approximately 44%. CSR disclosure, averaging 63%, was found to act as a moderator that strengthens the positive influence of green accounting and company size but weakens the negative influence of environmental performance and green innovation on profitability. These findings suggest that sustainability strategies have not yet fully generated positive synergies for profitability if they are not aligned with market readiness and the efficiency of corporate resource integration.